2010
DOI: 10.1016/j.immuni.2010.04.004
|View full text |Cite
|
Sign up to set email alerts
|

The Transcription Factor GATA3 Actively Represses RUNX3 Protein-Regulated Production of Interferon-γ

Abstract: SUMMARY The transcription factor GATA3 is crucial for the differentiation of naïve CD4+ T cells into T helper 2 (Th2) cells. Here we show that deletion of Gata3 allowed the appearance of interferon γ (IFNγ)-producing cells in the absence of interleukin-12 (IL-12) and IFNγ. Such IFNγ production was transcription factor T-bet-independent. Another T-box-containing transcription factor Eomes, but not T-bet, was induced both in GATA3-deficient CD4+ T cells differentiated under Th2 cell conditions, and in Th2 cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
163
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 154 publications
(171 citation statements)
references
References 45 publications
7
163
1
Order By: Relevance
“…The cells with decoupled proliferation and effector cytokine response show increased expression of GATA-3. Overexpression of GATA-3 alters the relative expression between T-bet and GATA-3 and perhaps suppresses cytokine production by decoupled HA-specific CD4 + T cells, in ways similar to the known suppression of IFN-g production in T-bet-expressing CD4 + T cells by GATA-3 overexpression (24,25). However, the reason for suppression of IL-4 production in GATA-3-overexpressing decoupled HA-specific CD4 + T cells is not clear.…”
Section: Discussionmentioning
confidence: 91%
“…The cells with decoupled proliferation and effector cytokine response show increased expression of GATA-3. Overexpression of GATA-3 alters the relative expression between T-bet and GATA-3 and perhaps suppresses cytokine production by decoupled HA-specific CD4 + T cells, in ways similar to the known suppression of IFN-g production in T-bet-expressing CD4 + T cells by GATA-3 overexpression (24,25). However, the reason for suppression of IL-4 production in GATA-3-overexpressing decoupled HA-specific CD4 + T cells is not clear.…”
Section: Discussionmentioning
confidence: 91%
“…However, none of these settings showed essential functions of Eomes for the induction of IFN-g, probably due to compensatory effects of the related transcription factor Tbet (21,22,57). Indeed, Eomes can be expressed by T-bet-deficient T cells and partially replace T-bet function (8,23,24,57). Although T-bet is not required for Eomes expression, it can enhance it by preventing the expression of known inhibitors of Eomes such as GATA3 (9,23,60).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Eomes can be expressed by T-bet-deficient T cells and partially replace T-bet function (8,23,24,57). Although T-bet is not required for Eomes expression, it can enhance it by preventing the expression of known inhibitors of Eomes such as GATA3 (9,23,60). According to redundant functions between Eomes and T-bet, we did not observe differences in the accumulation of Eomes-deficient Th1 cells under inflammatory conditions or under steady state, despite the fact that the majority of Eomes + WT cells under those conditions were active producers of IFN-g.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Yagi et al (39) reported high levels of Eomes and IFN-g secretion in Gata3-deficient CD4 T cells cultured under Th2 conditions. They concluded that Gata3 blocks the Runx3-Eomes-IFN-g pathway, presumably through interaction with Runx3.…”
Section: Discussionmentioning
confidence: 99%